(untitled) (Journal of Nobel Medical College, 2022)
Background: Corona Virus Disease 2019came into existence in December 2019, as a sudden outbreak inthe city of Wuhan, China. Early identification of the patient is vitalto control disease transmission.This study is aimed at estimatingthe sensitivity, specificity, and practicability of Highresolution computed tomography chest in detecting Corona Virus Disease 2019 compared with a Reverse transcriptase-polymerase chain reaction. Materials and Methods: This was a retrospective single-center analytical study conducted at Nobel Medical Collegefor5 months during the second wave of Covid 19 from Feb 2021 to June 2021 after ethical approval from the Institutional Review Committee of Nobel Medical College Teaching Hospital. All clinically suspected patients who had undergoneHigh-resolution computed tomography chest and Reverse transcriptase-polymerase chain reaction within a 1-week time difference were included. High-resolution computed tomography chest scan was reported before Reverse transcriptase-polymerase chain reaction results became available. Results: Among 342 consecutive patients (195 male and 147 females, mean age 64), Reverse transcriptase-polymerase chain reaction was positive in 183 (53.5%) cases. Common High-resolution computed tomography chest features significantly more common in Reverse transcriptase-polymerase chain reaction positive patients were bilateral subpleural and peripheral ground-glass opacities with septal thickening(crazy paving). In comparison with Reverse transcriptase-polymerase chain reaction, the sensitivity was 91.8% and specificity 67.2%. Conclusion: This study revealed the high sensitivity of high-resolution computed tomography chest scansin accurately diagnosingCorona Virus Disease 2019.